142k views
5 votes
Simplify the expression: (3.45× 10-²) ÷ (2.03 x 10-⁵)

User Nermeen
by
5.5k points

1 Answer

6 votes

Recall that we want to solve this problem


(3.45\cdot10^(-2))/(2.03\cdot10^(-5))

We will use the following property, given a nonzero number a and numbers b,c we have that


(a^b)/(a^c)=a^(b-c)

So if we divide two numbers that have the same base, we can simply subtract their exponents.

So, using the properties of multiplication of fractions, we get


(3.45\cdot10^(-2))/(2.03\cdot10^(-5))=(3.45)/(2.03)\cdot(10^(-2))/(10^(-5))=(3.45)/(2.03)\cdot10^(-2-(-5))=(3.45)/(2.03)\cdot10^3^{}

With help of a calculator, we will calculate 3.45/2.03. By doing so, we get that


(3.45)/(2.03)=1.6995073

So we have


(3.45\cdot10^(-2))/(2.03\cdot10^(-5))=1.6995073\cdot10^3=1699.5073

User Rob Davis
by
4.5k points